2019
DOI: 10.1370/afm.2401
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Flash-Mob Study for Suspected Acute Coronary Syndrome

Abstract: PURPOSE Our primary objective was to evaluate the Marburg Heart Score (MHS), a clinical decision rule, or to develop an adapted clinical decision rule for family physicians (FPs) to safely rule out acute coronary syndrome (ACS) in patients referred to secondary care for suspected ACS. The secondary objective was to evaluate the feasibility of using the flash-mob method, an innovative study design, for large-scale research in family medicine. METHODSIn this 2-week, nationwide, prospective, observational, flash-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…These studies showed mediocre discriminatory properties (C-statistic 0.66–0.72), and unaided clinical judgement provided a better overall fit (C-statistic of 0.75), with poor agreement in risk estimation (in half of cases) [ 6 , 17 , 18 ]. Recently, a 2-week flash-mob study was performed among Dutch GPs in which the Marburg Heart Score was evaluated for its properties for ruling out ACS in patients referred for suspected ACS [ 19 ]. Overall, the diagnostic properties in terms of predictive values of the Marburg Heart Score, as for the other risk assessment tools, were not superior to unaided GP assessment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed mediocre discriminatory properties (C-statistic 0.66–0.72), and unaided clinical judgement provided a better overall fit (C-statistic of 0.75), with poor agreement in risk estimation (in half of cases) [ 6 , 17 , 18 ]. Recently, a 2-week flash-mob study was performed among Dutch GPs in which the Marburg Heart Score was evaluated for its properties for ruling out ACS in patients referred for suspected ACS [ 19 ]. Overall, the diagnostic properties in terms of predictive values of the Marburg Heart Score, as for the other risk assessment tools, were not superior to unaided GP assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Schols et al. conducted a nationwide flash-mob study in the Netherlands to evaluate the safety of the Marburg Heart Score (MHS) to rule out ACS [ 20 ]. The MHS is a clinical decision rule based on five signs and symptoms, which was designed to identify patients with a low probability of ACS as the underlying cause of chest pain in the primary care population [ 21 , 22 ].…”
Section: Biomarkers In Diagnosis and Risk Stratification Of Nste-acsmentioning
confidence: 99%
“…Een sneltest die 45 euro zou kosten, zou tot 40% reductie van deze fout-positieven moeten leiden om kostenneutraal te zijn. 23 Iedere 1% verdere daling van de achteraf onterechte verwijzingen zou een kostenbesparing van 1 miljoen euro opleveren. In een prospectief onderzoek vonden we dat een beslisregel bestaande uit enkele van de best voorspellende symptomen én een H-FABP-sneltest een iets hogere negatief voorspellende waarde had dan de huisarts zónder aanvullende beslisregel of biomarkertest (97,2% versus 95,8%).…”
Section: Rapida-onderzoekunclassified